Gambaran Konsep Diri Anak Asuh di Panti Sosial PSAA 3 Ceger Jakarta Timur - Sukmawati, Ellies (Social Welfare Study Program, 2016)
One of the challenges for social institutions to prepare foster children ready for their social life is in the process of formation and development of self-concept in children fosterage because these children do not have parents/family. This self-assessment concept picture using a qualitative approach to explore the concept of self-perception in children orphanage which is a cross-nursing, or children who have never known and the affection of his parents. llustration of this concept in terms of three factors: knowledge, judgment and hope that they perceived as a characteristic of the concept itself, and to know the description of these three things unearthed by 9 aspect ability to be critical, self identity, self-image, behavior, physical, moral self, social self, respect self, the ego of individuals in the family. The results of this study can be used as an instrument to create a model of care Alternatives which uses colleague system that gives a positive value in the development of self-concept of children in the orphanage, because they do not have a figure that is nurturing or loving as a parent, so that a sense of the need they can get from the friendship are mutually supportive and mutually reinforcing them. Keywords: Children orphanage which is a cross-nursing (anak lintas panti), positive self-concept, negative self-concept.